Soil-site characterization on crop productivity in Alfisols of Eastern Ghats of Tamil Nadu, India - SRINIVASAN, R.; HEGDE, RAJENDRA; THILAGAM, V. KASTHURI; KUMAR, S. NAVEEN (Journal of Soil and Water Conservation, 2022)
The effect of toposequence, crop cultivation, and soil conservation practices on runoff and soil loss was investigated in Alfisols of South-Eastern Ghats (SEG) of Tamil Nadu using large-scale soil mapping (1:10000 scale) information. Major landforms on peninsular granite gneiss are divided into hillside slope (P1), foothills (P2), upper pediment (P3), and lower pediment (P4). Major land uses are mango, ragi, pulses, groundnut, sorghum, little millet, and forest. A detailed soil survey was done undertaking a profile study in each landform. Soil samples were collected from different horizons of soil profiles and analyzed different soil properties. Soils were shallow (<50 cm) to deep (100-150 cm), well-drained, nongravelly to gravelly, slightly acidic to slightly alkaline (pH 5.71 to 8.29) in reaction and non-saline (EC 0.03 to 0.25 dS m-1). The soil texture varied from loamy sand to sandy clay loam with rich organic carbon in surface soils and decreasing with soil depth. Cation exchange capacity (CEC) and base saturation (BS) were ranged from 2.81 to 13.82 cmol (p+) kg-1 and 46 to 98% respectively. Soils are classified into Typic Haplustalfs (P1), Lithic Haplustalfs (P2), Kanhaplic Haplustalfs (P3), and Kanhaplic Rhodustalfs (P4) under different landforms. Results revealed that significant soil erosion was associated with slope position and crop management in SEG. Hence, adaptation of appropriate soil and water conservation measures and the land-use system could reduce soil erosion and ensure crop productivity.